Convective Heat Transport in Bidirectional Water Driven Hybrid Nanofluid Using Blade Shaped Cadmium Telluride and Graphite Nanoparticles under Electromagnetohydrodynamics Process. (31st July 2022) - Ahmad, Iftikhar; Zan-Ul-Abadin, Qazi; Faisal, Muhammad; Loganathan, K.; Javed, Tariq; Namgyel, Ngawang
Abstract : The recent progress in nanotechnology provides the concept of hybrid-class nano-fluids having advanced thermal features comparing to regular nanofluids. The idea of a hybrid nanofluid has motivated many researchers because of its convincible performance in thermal systems. The novel theme of the present effort is to scrutinize the consequences of convective heat transfer in bidirectional water driven hybridclass nanofluid involving blade shaped cadmium telluride CdTe and graphite C nanoparticles with electromagnetohydrodynamics (EMHD) process. The transport equations representing the aforementioned topic are firstly nondimensionalized by using scaling-group transformation and then tackled by the Keller-box method, numerically. The significant results for pertinent parameters have been simulated and presented graphically as well as in tabular forms. Coefficients of drag forces are diminished with the more loadings of cadmium telluride and graphite nanoparticles and opposite results are noticed in the case of the Nusselt number. Heat transport has been improved significantly with more loadings of nanoparticles from 1 wt% to 10 wt%. A comparison benchmark for a limited version of the investigation is made with the previously published data.